Ruth's journey ebook The authorized novel of mammy from margaret mitchell's gone with the wind. - McCaig, Donald (Gone With the Wind, 2014)
"Exquisitely imagined, deeply researched . . . brings to the foreground the most enigmatic and fascinating figure in Gone with the Wind . This is a brave work of literary empathy by a writer at the height of his powers, who demonstrates a magisterial understanding of the period, its clashing cultures, and its heartbreaking crises. " —Geraldine Brooks, author of March The only authorized prequel to Margaret Mitchell's Gone with the Wind —the unforgettable story of Mammy. On a Caribbean island consumed by the flames of revolution, an infant girl falls under the care of two French émigrés, Henri and Solange Fournier, who take the beautiful child they call Ruth to the bustling American city of Savannah. What follows is the sweeping tale of Ruth's life as shaped first by her strong-willed mistress, and then by Solange's daughter Ellen and Gerald O'Hara, the rough Irishman Ellen chooses to marry; the Butler family of Charleston and their unexpected connection to Mammy Ruth; and finally Scarlett O'Hara—the irrepressible Southern belle Mammy raises from birth. As we witness the lives of three generations of women, gifted storyteller Donald McCaig reveals a nuanced portrait of Mammy, at once a proud woman and a captive, a strict disciplinarian who has never experienced freedom herself. Through it all, Mammy endures, a rock in the river of time. Set against the backdrop of the South from the 1820s until the dawn of the Civil War, here is a remarkable story of fortitude, heartbreak, and indomitable will—and a tale that will forever illuminate your reading of Margaret Mitchell's Gone with the Wind .